2008
DOI: 10.1007/s00423-008-0444-x
|View full text |Cite
|
Sign up to set email alerts
|

Staged lavage versus single high-volume lavage in the treatment of feculent/purulent peritonitis: a matched pair analysis

Abstract: Patients with secondary fecal or purulent peritonitis in at least two quadrants, undergoing a one step surgical repair including source control, primary anastomosis, and single high-volume lavage with more than 25 l have a comparable outcome to patients treated by staged lavage at significantly lower OR and ICU-utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
1
4
0
5
Order By: Relevance
“…We have shown that the use of larger volumes of intraoperative peritoneal irrigation offered no mortality benefit, regardless of the mechanism of injury, or the presence or severity of abdominal contamination as determined by the operating surgeon. This confirms similar findings in other populations (as stated above), and is a significant departure from the original evidence for its use at the beginning of the previous century [3][4][5][21][22][23][24]. The reason for this discrepancy is unclear, factor possibly involved include the use of antibiotics, improvements in surgical technique and the advent of critical care units.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…We have shown that the use of larger volumes of intraoperative peritoneal irrigation offered no mortality benefit, regardless of the mechanism of injury, or the presence or severity of abdominal contamination as determined by the operating surgeon. This confirms similar findings in other populations (as stated above), and is a significant departure from the original evidence for its use at the beginning of the previous century [3][4][5][21][22][23][24]. The reason for this discrepancy is unclear, factor possibly involved include the use of antibiotics, improvements in surgical technique and the advent of critical care units.…”
Section: Discussionsupporting
confidence: 85%
“…It has since become part of the algorithm for any laparotomy, including the operative management of abdominal trauma. Multiple case reports and contemporary experts' opinions have been lodged in the biomedical literature over the course of the subsequent century, with subsequent variable and sometimes conflicting recommendations [3,5,9,24]. All however share (with little more than anecdotal evidence to support those claims) the same purported benefit: decreased bioburden on the peritoneal surface, by either mechanical removal of bacteria and other soilings or supposed bacteriolytic properties of the effluent, to prevent intrabdominal abscess formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the OA treatment with NPWT represents a single arm study without any control group, so there is no way to determine if the rate of fistula would have been different with another treatment. Furthermore in one of both clinics including the majority of patients, single high volume lavage with primary closure of the fascia was preferred in the treatment of secondary peritonitis as published by our group in 2009 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…des Eingriffs empfiehlt sich eine Lavage des Abdomens, da hierdurch eine signifikante Verringerung der Keimzahl erreicht wird [1]. Der vorliegende Fall zeigt ein mögliches therapeutisches Vorgehen bei Patienten mit Koinzidenz von infrarenalem Bauchaortenaneurysma und Kolonkarzinom.…”
unclassified